Penerapan Kooperatif Learning pada Materi Irisan Kerucut dalam Meningkatkan Aktivitas, Prestasi Siswa SMKN 1 Sungai Kunyit - Ervi Mustika; Ahmad Yani T (Departement of Mathematics Education, 2024)
The aim of this research is to increase students' motivation and achievement regarding the concept of conic sections in mathematics subjects. One of the efforts made so that students better understand the conic section material is the cooperative learning method. This research includes class action research (PTK). This research uses a quantitative research approach with a survey method, through observations of 22 class XII students at SMKN 1 Sungai Kunyit, who were the research subjects. Data was collected during the learning process and through two stages of observation. The research results showed that in observation I the percentage of students who carried out positive activities was 50%. Meanwhile, in observation II, the percentage of students who carried out positive activities was 73%. Thus, there has been an increase in students' learning motivation as seen from the positive activities carried out during the observation process such as listening to teacher explanations, reading, doing practice questions, expressing opinions and participating in groups. The research results also show an increase in student achievement seen from the value of products and practices. Observation I percentage of product value 73.61% practical value 76.38%. In observation II the product value was 94.44% and the practice value was 97.44%.